SOCIAL COMPETENCY OF MECHANICAL ENGINEERING EDUCATION STUDENTS UNIVERSITY OF SARJANAWIYATA TAMANSISWA YOGYAKARTA - Nurcholish Arifin Handoyono; Rabiman Rabiman (Universitas Sultan Ageng Tirtayasa, 2018)
This studi aimed to determine the level of the social competence of the students of The Mechanical Engineering Education of Sarjanawiyata Tamansiswa University. This study is descriptive research. The study was conducted in Vocational Education School that became a parner in the implementation Magang III. The populations were students of The mechanical Engineering Education of Sarjanawiyata Tamansiswa University who were implementation of the Magang III in academic year 2017/2018 as many as 88 people. Data collected using the questionnaire method. As the data source is students of The mechanical Engineering Education of Sarjanawiyata Tamansiswa University as many as 72 people, teacher as Magang III tutor as many as 72 people, and students of Vocational Education School as many as 316 people. Analysis using descriptive statistics. The results show that the social competence of the students of The Mechanical Engineering Education of Sarjanawiyata Tamansiswa University are: 1) according to the students of The Mechanical Engineering Education of Sarjanawiyata Tamansiswa University is in “enough” category with an average value of 35,02%; 2) according to teacher as Magang III tutor is in “enough” category with an average value of 27,33%; and 3) according to students of Vocational Education School is in “enough” category with an average value of 27,41%.